Of Modern Technologies in Rehablitation - Azimovich, Berdiev Umidjon (American Journal of Botany and Bioengineering, 2025)
This article analyzes the effectiveness of modern methods of rehabilitation of stroke patients, we studied the data of domestic and foreign scientific sources. As a result of the work carried out, a number of techniques with the greatest evidence base were identified, as well as techniques with unproven efficacy and not recommended for use to improve the function of the upper limb in patients with stroke were established. Let’s consider them sequentially. The patient’s quality of life largely depends on the degree of restoration of the lost functions. In turn, the degree of their recovery depends on the timing of the beginning, dosage and continuity of the initiated rehabilitation measures.The statistics continue to indicate that cerebrovascular diseases remain one of the most important medical and social problems of modern society. Rehabilitation of cerebral stroke, despite effective diagnosis and quality treatment, is not always effective enough, partly due to the fact that the patient rehabilitation system in our country is not sufficiently developed. At the same time, over the past decade, developments based on the use of digital technologies, computerized systems and robotic devices have been added to the traditional methods of rehabilitation.